Comparative evaluation of two chelating agents in collagen fiber network modification over dentinal tubules: An in vitro analysis - Abdul Samad Khan; Imran Farooq; Saqib Ali; Soban Qadir Khan; Abbas Saeed Hakeem (Elsevier, 2020)
Objective: To compare effectiveness of ethylenediaminetetraacetic acid (EDTA) and citric acid in removing collagen fiber network covering dentinal tubules of human teeth. Materials and Methods: Eighteen dentin discs were divided in three groups; Gp 1: discs received no treatment (control), Gp 2: discs etched with 17% EDTA (pH = 7.1), and Gp 3: discs etched with 6 wt% citric acid (pH = 4.0). Scanning electron microscopy (SEM) was performed to assess collagen fiber removal and X-ray diffraction (XRD) was implemented to analyse crystal peaks of discs. Results: The SEM analysis demonstrated more collagen removal with EDTA treatment compared to citric acid treated specimens. Grade 6 (81% to 100% fiber removal) was mostly achieved for Gp 2 samples whereas grade 2 (1% to 20% fiber removal) was mostly achieved for Gp 3 samples and inter-group comparisons between these groups were statistically significant (p < 0.05). X-ray diffractogram of control and experimental samples demonstrated absence of calcite phase in experimental groups. The change in peak shapes and intensities were observed and citric acid treated samples revealed more intense peaks than EDTA group. Conclusion: Our study found 17% EDTA to be more effective in removing collagen fibers when matched with 6% citric acid.